POLA KOMUNIKASI NONVERBAL GURU DALAM PROSES BELAJAR MENGAJAR BAGI SISWA TUNARUNGGU DI SEKOLAH LUAR BIASA NEGERI PEMBINA PEKANBARU - Septia Mantari Putri; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Deaf are those with disorders of the senses of hearing, so the hearing was low once could not even hear what was said or what was delivered to him. Deaf students using nonverbal language to communicate. Patterns of Extraordinary elementary teacher communication used in the learning processis expected to change the mindset of deaf students and be able to interpret the message properly. To achieve the desired things, require s the teacher as a teacher must have the ability in nonverbal language and articulation (spellingwords) verbally. This study aims to look at the communication patterns of teachers in teaching and learning for deaf students in the State Special School Pembina Pekanbaru.This is a descriptive qualitative research. The objectof the researchisthe pattern of teacher nonverbal communication of State Special School Pembina Pekanbaru with research subjects who meet the research needs of as many asseven people consisting of the headmaster and teachers. The techniques used to collect the data were deep observation, interview and documentation.The results of this research are the pattern of teacher communication using multiple nonverbal messages for deaf students comprising kinesik message, the message proksemik, and paralinguistic messages that can support the learning process. Kinesik message consist of facial expressions, using body partsand body language to communicate. Proksemik message that the use of spaceas a measure of familiarity between students and teachers to communicate. Paralinguistic message consists of volume, eloquence and articulation of words. In using nonverbal messages of teachers in teaching, there are several obstacles faced such difficulties teachers tocope with difficult students understand so must use a standard language, and create a learning environmentas comfortable as possible for the students classified as active and quickly bored.Keywords : Nonverbal Communication, Communication Patterns, Deaf Students